Analysis of Science Literacy Skills Students of Class V Elementary School and Factors That Background IT - Rukoyah, Rukoyah; Agustin, M.; Sopandi, Wahyu; Sujana, Atep (International Conference on Elementary Education, 2020)
This study aims to describe the scientific literacy ability of elementary school students in class V and the factors form of the background of the ability of scientific literacy in elementary school students.One way to improve the quality of education in Indonesia is through increase scientific literacy learning. Learning scientific literacy is very important for students to understand what is learned. The instruments used were tests and interviews.The test given to students in the form of questions about the description of scientific literacy on ecosistem material. The study sample consisted of 42 students in class V SDN 1 Tangkil with 25 female students, 17 male students, Susukan District Cirebon District in 2018/2019 school year. From the results of tests on students' scientific literacy abilities, and interviews conducted with students, shows that elementary students' scientific literacy skills are still low